Reflexiones sobre 16 años en la Selva de Pino Paraná - Cockle, Kristina; Bodrati, Alejandro; Bonaparte, Bianca; Di Sallo, Facundo; Lammertink, Martjan (Revista Aves Argentinas, 2019)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).